Recovery of paddy soil methanotrophs from long term drought. (September 2015) - Collet, Sebastian; Reim, Andreas; Ho, Adrian; Frenzel, Peter
Abstract: Air-dried paddy soils stored for 1–18 years were used to examine the resistance of methanotrophs to drought. Older air-dried soils representing longer-lasting drought events reduced methanotrophic diversity, and adversely affected methane oxidation rate after re-wetting. In early incubations the type II methanotrophs are outperformed by the less abundant type I. Highlights: Even after two decades of drought some methanotrophs were still viable. Methylobacter are initial colonizers, recovering faster than Type II methonotrophs. Type I show highest relative pmoA gene expression levels.